Loss of ALDH18A1 function is associated with a cellular lipid droplet phenotype suggesting a link between autosomal recessive cutis laxa type 3A and Warburg Micro syndrome. Issue 4 (11th March 2014) - Handley, Mark T.; Mégarbané, André; Meynert, Alison M.; Brown, Stephen; Freyer, Elisabeth; Taylor, Martin S.; Jackson, Ian J.; Aligianis, Irene A.
Abstract Autosomal recessive cutis laxa type 3A is caused by mutations in ALDH18A1, a gene encoding the mitochondrial enzyme ∆1‐pyrroline‐5‐carboxylate synthase (P5CS). It is a rare disorder with only six pathogenic mutations and 10 affected individuals from five families previously described in the literature. Here we report the identification of novel compound heterozygous missense mutations in two affected siblings from a Lebanese family by whole‐exome sequencing. The mutations alter a conserved C‐terminal domain of the encoded protein and reduce protein stability as determined through Western blot analysis of patient fibroblasts. Patient fibroblasts exhibit a lipid droplet phenotype similar to that recently reported in Warburg Micro syndrome, a disorder with similar features but hitherto unrelated cellular etiology.